STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN NUMERASI SISWA PADA PEMBELAJARAN MATEMATIKA DASAR DI SEKOLAH DASAR - Ahmad Taufik; Lalu Hasan Ashari; Lalu Heri (Lembaga Berugak Baca, 2026)
Numeracy skills are essential competencies that enable students to understand, apply, and interpret mathematical information in everyday life. However, the numeracy abilities of elementary school students remain a significant challenge that requires continuous attention. This study aims to describe the strategies employed by teachers to improve students' numeracy skills in basic mathematics learning. The research adopted a qualitative approach using a descriptive method. The participants consisted of elementary school teachers and students selected through purposive sampling. Data were collected through observations, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented several key strategies to enhance students' numeracy skills, including the use of concrete learning media, contextual learning approaches connected to daily life experiences, gradual problem-solving exercises, collaborative group discussions, and the utilization of simple educational technology. These strategies contributed to increasing student engagement in the learning process, strengthening conceptual understanding of mathematics, and improving students' ability to solve numeracy-related problems effectively. The study concludes that the improvement of students' numeracy skills is strongly influenced by teachers' creativity in selecting instructional strategies that align with students' characteristics and learning needs